Study on a nano-porous gold/polyamidoamine (NPG/PAMAM)-based electrochemical aptamer biosensor for the detection of ochratoxin a in the red wine - Wensi, Zhang; Chuanjin, Cui; Chen, Hongshuo; Xuechao, Zhang; Junhui, Du (Food additives & contaminants. Part A, Chemistry, analysis, control, exposure & risk assessment, 2023)
In this study, a novel electrochemical aptamer sensor for detecting ochratoxin A (OTA) was constructed. First, a gold-copper alloy film was prepared via electrochemical deposition, and copper was selectively dissolved in constant potential mode for obtaining the nano-porous gold modified screen-printed carbon electrodes (NPG/SPCE). Then, 2-mercaptoethylamine was dropped on the NPG/SPCE surface and Au-S covalent bonds were formed for immobilizing the metal. Glutaraldehyde as cross-linking agent was added, which resulted in immobilization and attachment of PAMAM to the 2-mercaptoethylamine through the dehydration condensation reaction. During the preparation process, the nano-porous gold and PAMAM-modified layers were characterized by SEM, XRD, and IR spectroscopy, respectively. The characterization results showed that the nano-porous gold and PAMAM composite films were successfully modified. Finally, the OTA aptamer was cross-linked with PAMAM by glutaraldehyde to complete construction of the Apt/PAMAM/NPG/SPCE sensor. The electrochemical performance of this sensor was tested in ochratoxin A solutions with the DPV method. The results showed that the sensor's reproducibility, stability, and specificity were good. The spiked recoveries in red wine ranged from 99.65%∼101.6%, with a linear range of 0.5 ng/mL∼20 ng/mL and a minimum detection limit of 0.141 ng/mL. Thus, the novel biosensor may provide a promising tool for the trace detection of OTA.